2016
DOI: 10.1155/2016/3625279
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of p53 and p21 in Large Bowel Mucosa as Biomarkers of Inflammatory-Related Carcinogenesis in Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a chronic, relapsing inflammatory bowel disease that slightly increases the risk of colorectal cancer in patients with long-standing extended disease. Overexpression of p53 and p21 in colonic epithelia is usually detected in UC patients when no dysplasia is histologically seen and it is used by pathologists as a discriminator between regenerative changes and intraepithelial neoplasia, as well as a tissue biomarker useful to predict the risk of evolution toward malignancy. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
3
12
0
2
Order By: Relevance
“…This notion is validated by recent findings by Popp et al (34) showing that p53 overexpression (a biomarker of epithelial carcinogenesis) significantly correlated with architectural distortions of the crypts in UC (34). The results of Popp et al (34) seem to be in concert with the our findings, inasmuch as HGD in UC was mainly found in CCC.…”
Section: Discussionsupporting
confidence: 92%
“…This notion is validated by recent findings by Popp et al (34) showing that p53 overexpression (a biomarker of epithelial carcinogenesis) significantly correlated with architectural distortions of the crypts in UC (34). The results of Popp et al (34) seem to be in concert with the our findings, inasmuch as HGD in UC was mainly found in CCC.…”
Section: Discussionsupporting
confidence: 92%
“…The authors found that architectural distortion significantly correlated with p53 over expression [34].The results of Popp et al [34]seem to be in concert with the present findings,inasmuch as HGD in UC mainly occurred in crypts with architectural distortions (here referred to as CAD).…”
Section: Discussionsupporting
confidence: 86%
“…This notion is validated by recent findings showing that p53 over expression (a biomarker of epithelial carcinogenesis) significantly correlated with architectural distortions of the crypts in UC [34] …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Some immunohistochemical markers, such as p53, p21, bcl-2, AMACR (alpha methyl-CoA racemase), can be used to sustain a morphologic diagnosis of dysplasia [1,29]. Considering that treatment for UC-associated dysplasia is usually colectomy and there is a poor inter-and intraobserver agreement, especially for the diagnosis of LGD, it is mandatory that the diagnosis is confirmed by an independent expert pathologist before any invasive therapy [34][35][36].…”
Section: Dysplasiamentioning
confidence: 99%